Putting people at the centre of the circle: an agenda for behavioural research on the circular economy - Colley, Kathryn; Hague, Alice; Chen, Jianyu; Lorenzo-Arribas, Altea; Wooldridge, Tami; Somervail, Phoebe; Martínez Sánchez, Graciela; Assefa, Samuel; Bender, Fiona; Craig, Tony (Frontiers in Sustainability, 2024)
In a discourse characterised by technical innovation, alternative business models and material flows, the seemingly mundane, everyday forms of individual action towards circularity that can and are being taken by members of the public can sometimes feel overlooked. Whilst the importance of behaviour change is often acknowledged, in-depth conceptual engagement around circular behaviours remains uncommon in the field of circular economy research. In this perspective article we advocate for a person-centred perspective on circular behaviours, viewing people as not just consumers or users of circular products, but as individuals, nested within social groups, whose everyday, yet complex, relationships with material goods must undergo a shift if a circular economy is to be achieved. Drawing on insights from the wider field of pro-environmental behaviour research, we explore how we conceptualise circular behaviours themselves and how the behavioural theories we apply may constrain the ambition of the policy action our research supports. In doing so, we set out a person-centred agenda for research on circular behaviours, recommending 1) greater application of systems-oriented approaches; 2) conceptual development on categorizing circular behaviours, and 3) interdisciplinary efforts to integrate theory from across social science disciplines to underpin behavioural analyses and public engagement and action on the circular economy.emphasising the need for systems-oriented approaches and conceptual development drawing on insights from behavioural science and wider social science disciplines to underpin public engagement and action on the circular economy.